Keeping our core values ALIV[H]E. Holistic, community-led, participatory and rights-based approaches to addressing the links between violence against women and girls, and HIV - Hale, Fiona; Bell, Emma; Banda, Annie; Kwagala, Betty; van der Merwe, L Leigh-Ann; Petretti, Silvia; Yuvaraj, Anandi (Journal of virus eradication, 2018)
There is increasing recognition that violence against women is a barrier to sexual and reproductive health and rights, and a cause and consequence of HIV. In this viewpoint, we describe the recently published Action Linking Initiatives on Violence Against Women and HIV Everywhere (ALIV[H]E) framework [1]. The potential of this framework is explored in terms of it contributing to paradigm change to achieve the sexual and reproductive health rights of women experiencing, or living in contexts of, violence and/or HIV. We go on to suggest that a holistic approach t
Keywords: violence against women and girls; sexual and reproductive health rights; HIV